2022
DOI: 10.3389/fpls.2022.1003152
|View full text |Cite
|
Sign up to set email alerts
|

Efficient attention-based CNN network (EANet) for multi-class maize crop disease classification

Abstract: Maize leaf disease significantly reduces the quality and overall crop yield. Therefore, it is crucial to monitor and diagnose illnesses during the growth season to take necessary actions. However, accurate identification is challenging to achieve as the existing automated methods are computationally complex or perform well on images with a simple background. Whereas, the realistic field conditions include a lot of background noise that makes this task difficult. In this study, we presented an end-to-end learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…In a significant number of studies, new CNN architectures such as ResNet [30], AlexNet [33], and DenseNet [28], [34], with transfer learning are used to detect crop diseases. Few studies [35], [36], [37], [38], [39] suggested novel CNN architectures for the detection and classification of crop disorders. These approaches can yield accurate results with minimal preprocessing and computing costs.…”
mentioning
confidence: 99%
“…In a significant number of studies, new CNN architectures such as ResNet [30], AlexNet [33], and DenseNet [28], [34], with transfer learning are used to detect crop diseases. Few studies [35], [36], [37], [38], [39] suggested novel CNN architectures for the detection and classification of crop disorders. These approaches can yield accurate results with minimal preprocessing and computing costs.…”
mentioning
confidence: 99%